Differences in Linear Epitopes of Ara h 9 Recognition in Peanut Allergic and Tolerant, Peach Allergic Patients - Sánchez-Ruano, L.; Fernández-Lozano, C.; Ferrer, M.; Gómez, F.; de la Hoz, B.; Martínez-Botas, J.; Goikoetxea, M. J. (Frontiers in Allergy, 2022)
Background Peanut-allergic patients from the Mediterranean region are predominantly sensitized to the lipid transfer protein (LTP) Ara h 9, and the peach LTP Pru p 3 seems to be the primary sensitizer. However, LTP sensitization in peanut allergy is not a predictive marker for clinically relevant symptoms. Objective We aimed to identify sequential epitopes of IgE and IgG4 from Pru p 3 and Ara h 9 in peach-allergic patients sensitized to peanuts. We also sought to determine the differences in IgE and IgG4 binding between patients who had developed peanut allergy and those tolerating peanuts. Methods A total of 46 peach-allergic patients sensitized to peanuts were selected. A total of 35 patients were allergic to peanuts (peanut-allergic group) and 11 were tolerant to peanuts (peanut-tolerant group). We measured sIgE and sIgG4 in peanut, peach, and their recombinant allergen (Ara h 1, Ara h 2, Ara h 3, Ara h 8, and Ara h 9) with fluorescence enzyme immunoassay. We examined the IgE and IgG4 binding to sequential epitopes using a peptide microarray corresponding to linear sequences of the LTPs Ara h 9 and Pru p 3 with a library of overlapping peptides with a length of 20 amino acids (aa) and an offset of 3 aa. Results The frequency and the intensity of IgE recognition of Ara h 9 and Pru p 3 peptides were higher in the peanut-tolerant group than in the peanut-allergic group. We found four Ara h 9 peptides (p4, p14, p21, and p25) and four Pru p 3 peptides (p1, p3, p21, and p24) with a significantly elevated IgE recognition in peanut-tolerant patients. Only one peptide of Ara h 9 (p4) recognized by IgG4 was significantly elevated in the peanut-tolerant group. The IgG4/IgE ratio of Ara h 9 peptide 4 was significantly higher in peanut-tolerant patients than in peanut-allergic patients, while no significant differences were observed in the IgG4/IgE ratio of this peptide in Pru p 3. Conclusion Although we found significant differences in IgE and IgG4 recognition of Ara h 9 and Pru p 3 between peanut-tolerant and peanut-allergic patients (all of whom were allergic to peach), polyclonal IgE peptide recognition of both LTPs was observed in peach-allergic patients tolerating peanuts. However, the IgG4 blocking antibodies against Ara h 9 peptide 4 could provide an explanation for the absence of clinical reactivity in peanut-tolerant peach-allergic patients. Further studies are needed to validate the usefulness of IgG4 antibodies against Ara h 9 peptide 4 for peanut allergy diagnosis.